2021
DOI: 10.1037/bul0000349
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative dishonesty: A meta-analytic review.

Abstract: Although dishonesty is often a social phenomenon, it is primarily studied in individual settings. However, people frequently collaborate and engage in mutual dishonest acts. We report the first meta-analysis on collaborative dishonesty, analyzing 87,771 decisions (21 behavioral tasks; k = 123; n participants = 10,923). We provide an overview of all tasks used to measure collaborative dishonesty, and inform theory by conducting moderation analyses. Results reveal that collaborative dishonesty is higher (a) when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 124 publications
5
64
5
1
Order By: Relevance
“…This implies that participants were similarly inclined to lie to avoid punishment as they were to lie for prosocial reasons. This is somewhat in contrast with the meta-analysis of Leib et al (2021) showing that collaborative dishonesty tends to be higher when financial incentives are high. Moreover, previous research demonstrated that people are more willing to engage in deceptive behavior to avoid a loss than getting a reward (Schindler & Pfattheicher, 2017).…”
Section: Discussioncontrasting
confidence: 78%
“…This implies that participants were similarly inclined to lie to avoid punishment as they were to lie for prosocial reasons. This is somewhat in contrast with the meta-analysis of Leib et al (2021) showing that collaborative dishonesty tends to be higher when financial incentives are high. Moreover, previous research demonstrated that people are more willing to engage in deceptive behavior to avoid a loss than getting a reward (Schindler & Pfattheicher, 2017).…”
Section: Discussioncontrasting
confidence: 78%
“…Another line of research emphasizes the role of collective factors in driving dishonesty. These include settings in which one finds justification for one's own dishonesty in the dishonesty of peers [12,15,16]. The core insight here is that social reinforcement via observing and being observed by one's peers is interpreted as a signal of the dominant social norm, which can accelerate the contagion of dishonesty [1,8,44,45].…”
Section: Drivers Of Dishonestymentioning
confidence: 98%
“…We can turn to meta-studies to better understand what robustly predicts dishonest behavior. A recent meta-analysis [16] on collaborative dishonesty analyzed 87,771 decisions across 21 behavioral tasks by 10,923 participants. Meta-analytical results revealed various factors that increase collaborative dishonesty, including higher financial incentives, conducting a lab experiment rather than a field experiment, and absence of negative externalities of one's lies on others.…”
Section: Drivers Of Dishonestymentioning
confidence: 99%
See 2 more Smart Citations